2017
DOI: 10.1371/journal.pone.0178684
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of aplysin on liver tissue and the gut microbiota in alcohol-fed rats

Abstract: BackgroundThis study investigated the protective effect of aplysin on the liver and its influence on inflammation and the gut microbiota in rats with ethanol-induced liver injury.MethodsMale Sprague-Dawley rats were randomly assigned to an alcohol-containing liquid diet, control liquid diet or treatment with aplysin for 8 weeks. Hepatic and intestinal histopathological analysis was performed, and cytokine levels and the intestinal mucosal barrier were assessed. Enterobacterial repetitive intergenic consensus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
(42 reference statements)
2
14
0
Order By: Relevance
“…Ge et al also reported that aplysin had the hepatoprotective effect on oxidative damage caused by ethanol, which could prevent alcoholic liver injury [ 13 ]. Xue et al showed that aplysin could protect ethanol-induced hepatic injury, repair barrier function of the intestine and provide a low inflammatory response and a low level of plasma endotoxin [ 15 ]. Another study from a Chinese journal showed that the intestinal mucosal damage and lipid metabolism disorder caused by excessive iron exposure in rats were protected by aplysin [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ge et al also reported that aplysin had the hepatoprotective effect on oxidative damage caused by ethanol, which could prevent alcoholic liver injury [ 13 ]. Xue et al showed that aplysin could protect ethanol-induced hepatic injury, repair barrier function of the intestine and provide a low inflammatory response and a low level of plasma endotoxin [ 15 ]. Another study from a Chinese journal showed that the intestinal mucosal damage and lipid metabolism disorder caused by excessive iron exposure in rats were protected by aplysin [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal health was investigated and discussed by measuring the barrier function of intestinal mucosa and the level of plasma endotoxin. Alcohol induced the damage to the barrier function of intestinal mucosa, increased intestinal permeability resulted from endotoxin and other adverse factors, and contributed to the endotoxemia in alcoholic liver damage [ 15 , 18 ]. In this study, the plasma endotoxin level was significantly higher in the co-treatment of ethanol plus iron group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it inhibited apoptosis of enterocytes and modulated tight junction protein claudin-1, leading to improved gut integrity and endotoxemia; it also restored the antioxidant capacity of the liver and blocked the release of free fatty acids. Furthermore, aplysin from the red alga Laurencia tristicha was reported to revert the increased plasma endotoxin diamine oxidase (DAO) and fatty acid-binding protein 2 (FABP2) as well as the altered gut microbial composition in rats with ALD [ 85 ]. In another study, when administrated in a double layered microencapsulation, L. plantarum was shown to attenuate endotoxemia, normalize transaminases, reduce NF-κB and other cytokines, and restore the morphology and function of the gut and liver [ 27 ].…”
Section: Alcoholic Liver Disease (Ald)mentioning
confidence: 99%